2021
DOI: 10.1177/20543581211052731
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Versus Surgical Insertion of Peritoneal Dialysis Catheters: A Systematic Review and Meta-Analysis

Abstract: Background: Home-based peritoneal dialysis (PD) is an alternative to facility-based hemodialysis and has lower costs and greater freedom for patients with kidney failure. For a patient to undergo PD, a safe and reliable method of accessing the peritoneum is needed. However, different catheter insertion techniques may affect patient health outcomes. Objective: To compare the risk of infectious and mechanical complications between surgical (open and laparoscopic) PD catheter insertion and percutaneous catheter i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 97 publications
0
11
0
1
Order By: Relevance
“…This discrepancy might be attributed to the absence of antibiotic prophylaxis administered to patients undergoing percutaneous placement, unlike those undergoing surgical placement. Another meta-analysis by Anirudh Agarwal and al (15) comparing percutaneous insertion and surgical insertion (both laparoscopy and open surgery)…”
Section: Figure III Discussionmentioning
confidence: 99%
“…This discrepancy might be attributed to the absence of antibiotic prophylaxis administered to patients undergoing percutaneous placement, unlike those undergoing surgical placement. Another meta-analysis by Anirudh Agarwal and al (15) comparing percutaneous insertion and surgical insertion (both laparoscopy and open surgery)…”
Section: Figure III Discussionmentioning
confidence: 99%
“…20 There are various means of PD catheter placements (e.g., percutaneous, laparoscopic, and open/surgical catheter placement), varying in their invasiveness, postoperative pain, and recovery time. Agarwal et al 21 conducted a meta-analysis to compare the rates of complications among surgical and percutaneous insertion methods. They meta-analyzed two RCTs and 20 observational studies that found percutaneous insertion had significantly lower incidences of early infectious complications compared to surgical option.…”
Section: Discussionmentioning
confidence: 99%
“…28 More recently, a systematic review and meta-analysis that included both observational (non-randomised) studies and RCTs found that, in low certainty evidence, percutaneous PD catheter insertion may have been associated with lower risks of early (within 1 month) exit site infection (7 studies; RR 0.36, 95% CI 0.24-0.53) and overall exit infection (16 studies; RR 0.61, 95% CI 0.46-0.82), but little or no difference in tunnel infection (7 studies; RR 0.76, 95% CI 0.38-1.51) compared with surgical (open and laparoscopic) PD catheter insertion. 29 Prior to catheter insertion, it is advisable to carefully identify the optimal location of the exit site that will allow the patient to be able to see their exit site, clean it and avoid inadvertently traumatising it (e.g. by the belt).…”
Section: Catheter Placementmentioning
confidence: 99%